The Development of the Educational Game “Fraction Bakery ”: An Analysis of Media Advantages for Elementary School Students - Chrisnawati, Henny Ekana; Usodo, Budi; Nurhasanah, Farida; Sutopo, Sutopo; Kuswardi, Yemi (Journal of Mathematics and Mathematics Education, 2022)
This study aims to develop an educational game as a learning media for mathematics at the elementary school level, particularly fractions.  Named Fraction Bakery, this game was developed as a response to complaints of students' and teachers' difficulty in learning and teaching fractions. This difficulty, if poorly addressed, may serve as an iceberg-like issue for their understanding of more advanced mathematic concepts. Number recognition, including fractions, is fundamental to learning mathematics. As a teacher, it is necessary to evaluate such learning difficulties and seek alternative interactive learning media their students can enjoy. For the purpose of the study, the research and development model proposed by Thiagarajan, consisting of Define, Design, Development, and Disseminate stages, was applied. This game was still in the development process by evaluating the media value using trial responses involving undergraduate students of mathematics education at Sebelas Maret University. Regarding the product's interface, 71% of respondents gave a high score, 57% gave a very high score to the game animation, 75% stated that the game would likely motivate users to learn (affective impact), and 57% stated that the materials delivered in the game are highly relevant to the competency